Pecularities of Juvenile Sentencing - Margaryan, A. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The most difficult and crucial decision when dealing with juvenile justice is the choice of effective measures to address criminal behaviour of the juveniles. Usually, both general and special principles of sentencing are applied when making such a choice and especially – when sentencing a juvenile to a punishment. Special principles of sentencing are provided both by national and international regulations and are conditioned by the peculatities of the children due to their age, social, psychological and social status. However, the latter ones are not always fulfilled in Armenia because of the lacks and shortcomings of criminal legislation. First of all, this is a result of facile and abstract regulation of special rules of juvenile sentencing. The author justifies the necessity of detailed regulation of those requirements, which should be secured by competent authorities in the process of juvenile sentencing.
Keywords: punishment, sentencing principles, best interests of a child, efficiency of punishment, Beijing rules, wellbeing of a child